HEALTHY LIVING WITH A HEALTHY GYMNASTIC MOVEMENT FOR CHILDREN OF SUNGAI GEMPA - Noor Amaliah (Borneo Community Development, 2021)
ABSTRACT  Gymnastics is a very effective physical exercise to increase endurance. Healthy physical condition is characterized by physical fitness. Doing regular physical activity can increase a person's immunity and resistance, especially during the Covid-19 pandemic. This sporting activity is carried out to encourage people to increase endurance through aerobic exercise. This activity is a concrete manifestation of the KKN-M students of the Muhammadiyah University of Banjarmasin. The target of this activity is children in RT. 22 Sungai Gempa, Banjarmasin City. It is hoped that this activity can help increase endurance through exercise together.